2022
DOI: 10.1021/acs.jcim.1c01396
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dimeric hHv1 Model and Structural Bioinformatic Analysis Reveal an ATP-Binding Site Resulting in a Channel Activating Effect

Abstract: The human voltage-gated proton channel (hHv1) is a highly selective ion channel codified by the HVCN1 gene. It plays a fundamental role in several physiological processes such as innate and adaptive immunity, insulin secretion, and sperm capacitation. Moreover, in humans, a higher hHv1 expression/function has been reported in several types of cancer cells. Here we report a multitemplate homology model of the hHv1 channel, built and refined as a dimer in Rosetta. The model was then subjected to extensive Gaussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
0
3
2
Order By: Relevance
“…R219A) by using one‐way ANOVA with post hoc Tukey–Kramer test]. This result was inconsistent with a previously reported result (Llanos et al., 2022), which showed a slight effect of ATP on the R223A mutant of human‐Hv1. These inconsistencies may be attributed to the following: (1) we used mHv1 in this study, while they used human‐Hv1; and (2) multiple ATP‐binding sites may exist, and single‐point mutation experiments do not account for this possibility.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…R219A) by using one‐way ANOVA with post hoc Tukey–Kramer test]. This result was inconsistent with a previously reported result (Llanos et al., 2022), which showed a slight effect of ATP on the R223A mutant of human‐Hv1. These inconsistencies may be attributed to the following: (1) we used mHv1 in this study, while they used human‐Hv1; and (2) multiple ATP‐binding sites may exist, and single‐point mutation experiments do not account for this possibility.…”
Section: Discussioncontrasting
confidence: 76%
“…Although no significant difference was observed, a slightly weaker effect was noted in the R219A mutant than in the wild type (WT) [P = 0.0641 (WT vs. R219A) by using one-way ANOVA with post hoc Tukey-Kramer test]. This result was inconsistent with a previously reported result (Llanos et al, 2022), which showed a slight effect of ATP on the R223A mutant of human-Hv1. These inconsistencies may be attributed to the following: (1) we used mHv1 in this study, while they used human-Hv1; and…”
Section: Atp Influences the Activity Of Hv1 Through Direct Bindingcontrasting
confidence: 82%
See 2 more Smart Citations
“…Another important aspect about the ion channel is drug binding. MD simulations are used to explore ligand binding stability and to better assess the induced-fit effect from docking results , or to verify the binding poses from structural biology works. , Ligand-binding free energy calculations yield a quantitative profile for comparison with experimental measurements . In addition, the dynamical effects exerted by ligands can be accessed from simulation trajectories.…”
Section: Membrane Protein Simulationsmentioning
confidence: 99%